Attributable mortality of Stenotrophomonas maltophilia infections: a systematic review of the literature. (November 2009) - Falagas, Matthew E; Kastoris, Antonia C; Vouloumanou, Evridiki K; Rafailidis, Petros I; Kapaskelis, Anastasios M; Dimopoulos, George
Aim: Although Stenotrophomonas maltophilia is commonly isolated from clinical specimens, mainly of immunocompromised patients, mor tality directly attributable to this organism is controversial. We searched PubMed, Scopus and Cochrane and assessed the available literature regarding mortality attributable to infection with S. maltophilia .Method: Crude mortality and mor tality of case patients receiving appropriate or inappropriate initial antibiotic treatment were evaluated. A total of 15 ar ticles (six matched case––control, seven case––control and two controlled cohort studies) were identified; 13 studies (the six matched case––control and the seven case––control studies) were included in the analysis.Results: In seven studies, mortality of cases differed significantly from that of controls. Mortality was significantly higher in cases than controls in six of these studies; it was lower in cases than controls in the one study where controls had Pseudomonas aeruginosa bacteremia. In six studies, mortality of cases did not differ significantly compared with the respective controls. In three of four studies providing relevant data, mortality of cases treated with inappropriate initial antibiotic treatment was significantly higher compared with cases treated with appropriate initial antibiotic treatment.Conclusion: A considerable mortality rate (up to 37.5%) can be at tributed to S. maltophilia infection. Thus, clinicians should not underestimate the clinical significance of S. maltophilia infections.